2022
DOI: 10.1111/jam.15687
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Lactiplantibacillus fabifermentans and Furfurilactobacillus rossiae as potential cocoa fermentation starters

Abstract: Aims:To investigate the characteristics of two minority autochthonous LAB species, with particular regard to those properties that could be exploited in an improved cocoa fermentation process from a quality and safety point of view.Methods and Results: Bacterial, yeast and mould strains characteristic of spontaneously fermented Dominican cocoa beans were isolated and identified by 16S or 26S rRNA gene sequencing. The potential of two autochthonous strains of LAB belonging to the species Lactiplantibacillus fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…As temperatures increased, both species experienced significant declines in growth, culminating in a complete absence of growth at 45 °C. This pattern of thermosensitivity mirrors the observations of Korcari [ 29 ], who also reported that these bacteria tolerate temperatures up to 37 °C but show markedly reduced growth at 42 °C. On the other hand, in examining thermotolerance ( Table 3 ), AAB displayed a lower growth rate than LAB.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As temperatures increased, both species experienced significant declines in growth, culminating in a complete absence of growth at 45 °C. This pattern of thermosensitivity mirrors the observations of Korcari [ 29 ], who also reported that these bacteria tolerate temperatures up to 37 °C but show markedly reduced growth at 42 °C. On the other hand, in examining thermotolerance ( Table 3 ), AAB displayed a lower growth rate than LAB.…”
Section: Resultssupporting
confidence: 89%
“…The LAB species L. plantarum and L. fabifermentans were selected to assess their stress resistance. L. plantarum has been used as a starter culture to improve the production of volatile compounds [ 18 , 22 ]; while L. fabifermentans is known for its capacity to grow in low pH, elevated temperatures, and high osmotic pressure [ 29 ]. Similarly, the tolerance of the two AAB strains isolated was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this work is to evaluate the impact of adjunct cultures of selected lactic acid bacteria (LAB) on fermentation parameters, flavour, and sensory profile of fine cocoa and chocolate. In a previous research [11], we characterised the microbial population of spontaneously fermented Dominican cocoa beans, with the aim of selecting autochthonous LAB species, which are used as adjunct cultures that could improve the quality and flavour of the final chocolate. For these reasons, we focalized the attention on two minority LAB species isolated together with the dominant Lactiplantibacillus plantarum and Limosilactibacillus fermentum.…”
Section: Introductionmentioning
confidence: 99%